Thermo-mechanical viscoelastic characterization and modeling of 4D printed shape memory polymers - Israr Ud Din; Siddhesh S. Kulkarni; Kamran A. Khan (Polymer Testing)
The majority of existing literature focuses on the characterization and modeling of conventionally synthesized shape memory polymers (SMPs). This work presents a detailed systematic thermo-viscoelastic characterization framework required for modeling 4D printed structures. Initially, the thermal properties were investigated to understand the behavior of the 4D-printed SMP under varying temperatures. Subsequently, thermo-viscoelastic experiments were conducted at various strain rates under tension and compression, covering temperature ranges from 25°C to 65°C. These tests revealed a strong dependency of mechanical behavior on both time and temperature. The stress-strain plots of the test temperature below the glass transition temperature demonstrated a clear yield point followed by a post-yield stress-softening. Under room temperature testing, a lower failure strain of ∼4 % was recorded at the fastest strain rate of 0.1/s. Moreover, temperature sweep, stress relaxation, creep, coefficient of thermal expansion (CTE) and strain-controlled shape memory tests were performed using a dynamic mechanical analyzer (DMA). A shape fixity of ∼97 % and a recovery ratio of ∼99 % was obtained in the shape memory tests. Finally, the experimental results were successfully utilized to calibrate a thermo-viscoelastic model from the literature. The shape memory effects were predicted with reasonable agreement with the test data. The findings of this study can be used in the development of complex, intricate 4D structures, providing deeper insights into their design.